Artifacts in oral histopathology and causative factors - Fakhraie A (Tehran University Medical Journal, 1998)
Artifacts in histopathology, could create serios errors and cause misdiagnosis. In some cases, the degree of artifactual damage is so large that may involve the entire specimen, rendering it suboptimal or useless for diagnostic purposes. Usually, cases of oral cavity specimens are of small size and fine texture, and as a result, the astifacts are more effective on them. However, there are very limited reports in this respect. The present study included a relatively vast range of possible causative factors (which could cause artifacts in histiomorphology). 100 specimens went under the influences of 22 factors. We found that in common, causative factors with reports of Mehregan and Margarone our results are, somehow similar in other cases, which were for the first time applied to, the results were interesting and impressive for some kind of mucosal lesions such as pemphigoids are on malignant and premalignant lesions.